Long Strange Journey : On Modern Zen, Zen Art, and Other Predicaments - Levine, Gregory P. A.; Levine, Gregory P. A. (Book collections on Project MUSE., 2017)
The book presents an alternative history of modern-contemporary Zen and Zen art that emphasizes their unruly and polythetic-prototypical natures, taking into consideration serious religious practice and spiritual and creative discovery as well as conflicts over Zen's value amid the convolutions of global modernity, squabbles over authenticity, resistance against the notion of "Zen influence," and competing claims to speak for Zen art made by monastics, lay advocates, artists, and others